(untitled) (Research, Society and Development, 2025)
Aromatherapy, based on the use of essential oils extracted from plants, has proven effective in promoting relaxation, pain relief, reducing anxiety, and improving well-being during labor. Application methods, such as inhalation and massage, allow for the absorption of volatile compounds, which act directly on the limbic system, responsible for regulating emotions and hormone production. Therefore, the objective of this study is to present the main neurological mechanisms stimulated by aromatherapy during labor. The qualitative and exploratory research was conducted through a literature review in scientific databases such as PubMed and BVS, considering publications from the last ten years. The results show that oils such as lavender, chamomile, and sweet orange have anxiolytic, analgesic, and relaxing properties, helping the woman in labor experience childbirth in a more peaceful and humanized way. The activated neurological mechanisms involve the release of neurotransmitters such as oxytocin, serotonin, and endorphins, promoting natural analgesia and strengthening the mother-baby bond. Furthermore, aromatherapy reinforces women’s autonomy during childbirth and can be safely and cost-effectively incorporated into obstetric practices. It can be concluded that, when applied by trained professionals, this technique complements conventional care, fostering a welcoming, respectful environment that focuses on the pregnant woman’s emotional and physiological needs.